A Methodological Review of Tools That Assess Dust Microbiomes, Metatranscriptomes and the Particulate Chemistry of Indoor Dust - Yousef Nazzal; Fares M. Howari; Aya Yaslam; Jibran Iqbal; Lina Maloukh; Lakshmi Kesari Ambika; Ahmed A. Al-Taani; Ijaz Ali; Eman M. Othman; Arshad Jamal; Muhammad Naseem (Atmosphere, 2022)
Indoor house dust is a blend of organic and inorganic materials, upon which diverse microbial communities such as viruses, bacteria and fungi reside. Adequate moisture in the indoor environment helps microbial communities multiply fast. The outdoor air and materials that are brought into the buildings by airflow, sandstorms, animals pets and house occupants endow the indoor dust particles with extra features that impact human health. Assessment of the health effects of indoor dust particles, the type of indoor microbial inoculants and the secreted enzymes by indoor insects as allergens merit detailed investigation. Here, we discuss the applications of next generation sequencing (NGS) technology which is used to assess microbial diversity and abundance of the indoor dust environments. Likewise, the applications of NGS are discussed to monitor the gene expression profiles of indoor human occupants or their surrogate cellular models when exposed to aqueous solution of collected indoor dust samples. We also highlight the detection methods of dust allergens and analytical procedures that quantify the chemical nature of indoor particulate matter with a potential impact on human health. Our review is thus unique in advocating the applications of interdisciplinary approaches that comprehensively assess the health effects due to bad air quality in built environments.